A Case Report on Cleidocranial Dysplasia: Diagnosis and Treatment - Kolokitha, Olga-Elpis; Ioannidou, Ioulia (Perspective of Recent Advances in Medical Research Vol. 12, 2023)
We here in report a case of CCD that was not previously diagnosed because of the extremely low incidence of this disorder. A rare congenital autosomal dominant skeletal disorder called cleidocranial dysplasia (CCD) affects the skull. Human RUNX2, which can be found on the short arm of chromosome 6p21, has heterozygosity of mutations that cause the disorder. One per million live births is the incidence of CCD. About 40% of patients with the condition experience spontaneous onset of CCD, and one in three of these patients has unaffected parents. The most prevalent features associated with CCD are aplastic or hypoplastic clavicles, supernumerary teeth, failed eruption of permanent teeth, and a hypoplastic maxilla. A 13-year-old Caucasian boy was referred to the ortho- dontic clinic of the School of Dentistry, Aristotle University, Thessaloniki, Greece. The patient was subsequently diagnosed with CCD based on the clinical examination, panoramic X-ray, anterior-posterior and lateral cephalogram, and chest radiograph findings. The details of this case are herein reported because of the extremely low incidence of this disorder. The overall treatment goal is to establish functional occlu-sion and an aesthetic facial and dental appearance. Sometimes this disorder causes psychological problems for the patients; therefore, proper motivation and sup- port are important.